On the normality of families of space mappings with branching - Sevost'yanov, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We study space mappings with branching that satisfy modulus inequalities. For classes of these mappings, we obtain several sufficient conditions for the normality of families.